Gingival response to relief and non relief removable orthodontic appliances - Alaa D Al-Dawoody; Ghada Dh Al-Sayagh; Nada M Al-Sayagh (University of Mosul, College of Dentistry, 2005)
Abstract The gingival state of thirty seven young patients (mean age 11.6 years) wearing simple removable orthodontic appliances was assessed and followed at monthly intervals for 3 months. For 17 of the patients, intentional relief of the appliance was carried out in the upper right area. Statistically, the plaque index levels were similar in both "relief" and "non relief" groups and reached a similar score at 2 and 3 months. The gingival index was significantly higher in the "relief" group.